(untitled) (Zoo Botanica, 2025)
Medicago sativa L. is commonly known as alfalfa. It is a perennial legume crop of significant importance, as it is highly nutritious, and it can fix nitrogen in the soil. This study focuses on evaluating the productivity and quality of various alfalfa germplasms under growing conditions using the RCBD design. Statistical analysis such as Augmented RCBD ANOVA, LSD design, Genetic Advance percentage, Heritability percentage, and correlation analysis were performed in this experiment The key agronomic and quality parameters were recorded, such as germination %, crop stand, plant height, no. of tillers/plant, no. of tillers/meter row, and leaves/tillers. The quality traits are crude protein %, starch %, ash %, crude fiber %, moisture dry matter %, fat %, NDF %, and ADF %. In 2022, the seeds of 67 germplasms and one check Sargodha alfalfa 2011 while in 2023, the seeds of 214 germplasms and the same check Sargodha alfalfa 2011 were evaluated. During 2022, these four-germplasm lines, such as (Acc.#6477), (Acc.# 6333), (Acc.#6359), and (Acc.#6394), showed better performance in alfalfa germination percentage, while during 2023, these five-germplasm lines, such as (Acc.#6349), (PI 631584), (PI 631563), (PI 672793), and (PI 672804), showed better performance. Overall, this research provides valuable insights into the genetic variability and potential breeding strategies for improving alfalfa germplasm, and these nine germplasms can be grown in Pakistan to get better production and quality.